Psychological and Sociological Factors Weakening Public Budget Awareness - Fidan Kılavuz; Cihan Yüksel (International Journal of Public Finance, 2019)
Public budget, which is the total of the expenditures made to meet the common needs of the society and of the revenues obtained to finance these expenditures, can be expressed with a “common wallet” metaphor. However, the main problem is, in case that public resources are not used correctly and effectively, why citizens do not show as much sensitivity towards their common wallets, as they show towards their personal wallets. It is important to examine the factors that weaken public budget awareness (common wallet perception) on the basis of behavioral economics, which is an area that observes the effects of people's attitudes, behaviors, and thoughts on economic-based choices and decisions and examines these observations based on experiments. For this reason, the main purpose of our study has been to bring some concepts used in the fields of psychology and sociology in the field of public finance. In this study, the "fiscal alienation" concept was derived from the concept of lack of social belonging, “lack of fiscal altruistic punishment" concept from the concept of altruistic punishment, "fiscal bystander effect" from the concept of the bystander effect, "fiscal social loafing" concept from the concept of social loafing, "behavioral fiscal dissonance" concept from the concept of the theory of cognitive dissonance, and "the problem of fiscal ethic" concept from the concept of undeveloped ethical culture/behaviors.